FPGA-Based Modulation Technique for Five-to-Three-Phase Ultra Sparse Matrix Converter - Malakar T.; Siva V.; Singh S.K. (My University, 2025)
A five-phase permanent magnet synchronous generator is developed in our lab. To supply the generated five-phase power to the existing three-phase system, a five-to-three-phase variable frequency AC–AC converter is required, where the input would be variable frequency AC and the output side would be fixed line frequency AC. Five-to-three-phase ultra sparse matrix converter (USMC) is proposed to achieve the purpose. In this topology, power can flow from source to load side only. This topology comprises of eleven controlled devices only, and there is no requirement of DC-link capacitor. Hence, the size and cost of the converter are reduced compared to the conventional DC-link converters, and reliability is also increased. The proposed modulation technique has the property of zero current switching. This modulation scheme can produce constant frequency three-phase output from a variable five-phase frequency. The simulation of this modulation scheme is done and verified using XILINX system generator (XSG) toolbox in MATLAB Simulink. Less than 5% output voltage THD is achieved in simulation results. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.